Cartographie des pornographies critiques - Myriam Le Blanc Élie; Julie Lavigne; Sabrina Maiorano (Genre, Sexualité et Société)
Since the 1980s, in a corollary movement to the emergence of hardcore mainstream pornography, several women filmmakers (cisgender and transgender) produced critical pornography that is rooted in pro-sex feminism. Whether they are feminist, by and for women, by and for lesbians, queer, educational, alternative or indie, all of those pornographic productions contain a critical discourse on mainstream pornography. This article presents a review of critical pornography initiatives from the perspective of women director and as presented in the academic literature. In addition to identifying the different categories, we will focus on understanding the links between those initiatives and pro-sex feminist thought, as well as some of its specific indicators like women’s sexual agency, the centrality of feminine pleasure, and the subversion of mainstream pornography’s codes.